Two Novel Mutations Identified in an African-American Child with Chediak-Higashi Syndrome - Kerry Morrone; Yanhua Wang; Marjan Huizing; Elie Sutton; James G. White; William A. Gahl; Karen Moody (Case Reports in Medicine)
Background. Chediak-Higashi syndrome (CHS) is a rare, autosomal recessive disorder characterized by oculocutaneous albinism, immunodeficiency, coagulopathy and late-onset, progressive neurological dysfunction. It also has an “accelerated phase” characterized by hemophagocytic lymphohistiocytosis (HLH). The disease is caused by mutations in the CHS1/LYST gene located on chromosome 1, which affects lysosome morphology and function. We report the case of an African-American child with CHS in Case. This 16-month old African-American girl presented with fever and lethargy. The proband had pale skin compared to her parents, with light brown eyes, silvery hair and massive hepatosplenomegaly. Her laboratory evaluation was remarkable for pancytopenia, high serum ferritin and an elevated LDH. Bone marrow aspirate revealed large inclusions in granulocytes and erythrophagocytosis consistent with HLH. Genetic evaluation revealed two novel nonsense mutations in the CHS1 gene: c.3622C>T (p.Q1208X) and c.11002G>T (p.E3668X). Conclusions. Our patient is one of the few cases of CHS reported in the African American population. We identified 2 nonsense mutations in the CHS1 gene, the first mutation analysis published of an African-American child with Chediak-Higashi Syndrome. These two mutations predict a severe phenotype and thus identification of these mutations has an important clinical significance in CHS.